Caffeine as an analgesic adjuvant for acute pain in adults. - Derry, C; Derry, S; Moore, R (2012)
BACKGROUND: Caffeine has been added to common analgesics such as paracetamol, ibuprofen, and aspirin, in the belief that it enhances analgesic efficacy. Evidence to support this belief is limited and often based on invalid comparisons. OBJECTIVES: To assess the relative efficacy in acute pain of a single dose of any analgesic plus caffeine against the same dose of analgesic alone. SEARCH METHODS: We searched CENTRAL, MEDLINE, EMBASE, and the Oxford Pain Relief Database to January 2012, and also carried out Internet searches and contacted pharmaceutical companies known to have carried out trials that have not been published. SELECTION CRITERIA: We included randomised, double-blind studies that compared a single dose of analgesic plus caffeine with the same dose of the analgesic alone in the treatment of acute pain. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed eligibility and quality of studies, and extracted data. Any disagreements or uncertainties were settled by discussion with a third review author. We sought any validated measure of analgesic efficacy, but particularly the number of participants experiencing at least 50% of the maximum possible pain relief over four to six hours, participants reporting a global evaluation of treatment of very good or excellent, or headache relief after two hours. We pooled comparable data to look for a statistically significant difference, and calculated numbers needed to treat to benefit (NNT) with caffeine. We also looked for any numerical superiority associated with the addition of caffeine, and information about any serious adverse events. MAIN RESULTS: We identified 19 studies (7238 participants) in valid comparisons. Most studies used paracetamol or ibuprofen, with 100 mg to 130 mg caffeine, and the most common pain conditions studied were postoperative dental pain, postpartum pain, and headache. There was a small but statistically significant benefit with caffeine used at doses of 100 mg or more, which was not dependent on the pain condition or type of analgesic. About 5% to 10% more participants achieve a good level of pain relief (at least 50% of the maximum) with the addition of caffeine, giving a NNT of about 15.Most comparisons individually demonstrated numerical superiority with caffeine, but not statistical superiority. One serious adverse event was reported with caffeine, but was considered unrelated to any study medication.We know or suspect of the existence of 20 additional studies with 9785 participants for which data for analysis were not obtainable. The additional analgesic effect of caffeine remained statistically significant but clinically less important even if all the known missing data had no effect; that is not likely to be the case. AUTHORS' CONCLUSIONS: The addition of caffeine (≥ 100 mg) to a standard dose of commonly used analgesics provides a small but important increase in the proportion of participants who experience a good level of pain relief.